RESEARCH OF MARITAL RELATIONS IN EARLY MEDIEVAL SOGD BASED ON HISTORICAL DOCUMENTS (E Global Congress, 2024)
The article analyzes digital documents Nov 3. (marriage certificate in Sogd) and Nov 4. (duties of the groom to the bride), discovered in the archives of Mount Mug. These documents serve as a direct reflection of marriage relations in early medieval Sogd. The study is based on publications by V.A. Livshits, M. Ishakov, I. Gershevich and other authors. The historical and cultural context of marriage in Sogdian society, as well as the influence of Zoroastrianism on marital relations is considered. The study contributes to the understanding of social structure and family relations in ancient Sogd.